2003
DOI: 10.1017/s1355770x0300010x
|View full text |Cite
|
Sign up to set email alerts
|

Potential economic impacts of terminator technologies: policy implications for developing countries

Abstract: The terminator gene can render seeds sterile, so forcing farmers to purchase fresh seed every year. It is a technological solution to the problem of market failure that could increase the appropriability of R&D investment more effectively than intellectual property rights legislation or patents. This paper shows that appropriability should be more than tripled and that this leads to greater private R&D investment, which may be expected to double or triple. This would bring open-pollinating varieties into line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…11 Although PVP provide some incentives for increased plant breeding, evidence from some empirical studies show mixed results with some authors finding that it may not be strong enough to encourage plant breeding investments. [11][12][13][14] For example, Tripp et al 11 studied the potential of PVP to provide incentives for plant breeding in developing countries (China, India, Colombia, Kenya and Uganda). Their findings showed that development of PVP systems in developing countries should be framed as part of a broader strategy for seed system development, as PVP may not be adequate to initiate commercial seed development.…”
Section: International Experiences In Plant Variety Protectionmentioning
confidence: 99%
“…11 Although PVP provide some incentives for increased plant breeding, evidence from some empirical studies show mixed results with some authors finding that it may not be strong enough to encourage plant breeding investments. [11][12][13][14] For example, Tripp et al 11 studied the potential of PVP to provide incentives for plant breeding in developing countries (China, India, Colombia, Kenya and Uganda). Their findings showed that development of PVP systems in developing countries should be framed as part of a broader strategy for seed system development, as PVP may not be adequate to initiate commercial seed development.…”
Section: International Experiences In Plant Variety Protectionmentioning
confidence: 99%
“…Furthermore, companies apply other legal (e.g. patents, plant variety protection, and contract growing) and biological ways to make GM seeds excludable (Srinivasan and Thirtle, 2003). For example, with respect to biological methods of exclusion, companies prevent farmers from saving GM seed for future use.…”
Section: Seed Supply and Deliverymentioning
confidence: 99%
“…In addition to this, some empirical studies have argued that IPRs or PVP systems might not be strong enough to stimulate significant investments in plant breeding research and innovations [6,9,10]. For example, Tripp et al [6], based on case studies from China, Colombia, India, Kenya and Uganda, found that development of PVP systems in developing countries were inadequate for stimulating the development of the local commercial seed sector, and recommended that efforts need to be integrated into broader seed system development strategies.…”
Section: Introductionmentioning
confidence: 99%